Non-destructive linear model for leaf area estimation in Vernonia ferruginea Less - Souza, Marcelo Claro de [UNESP]; Amaral, Cárita Liberato do [UNESP] (Instituto Internacional de Ecologia, 2015)
Leaf area estimation is an important biometrical trait for evaluating leaf development and plant growth in field and pot experiments. We developed a non-destructive model to estimate the leaf area (LA) of Vernonia ferruginea using the length (L) and width (W) leaf dimensions. Different combinations of linear equations were obtained from L, L2, W, W2, LW and L2W2. The linear regressions using the product of LW dimensions were more efficient to estimate the LA of V. ferruginea than models based on a single dimension (L, W, L2 or W2). Therefore, the linear regression “LA=0.463+0.676WL” provided the most accurate estimate of V. ferruginea leaf area. Validation of the selected model showed that the correlation between real measured leaf area and estimated leaf area was very high.

A estimativa de área foliar é um importante traço biométrico para avaliação do desenvolvimento foliar e do crescimento vegetal em experimentos de campo e casa-de-vegetação. Foi desenvolvido um modelo linear não destrutivo capaz de estimar a área foliar (AF) de Vernonia ferruginea usando o comprimento (C) e a largura (L) foliar. Diferentes combinações de equações lineares foram obtidas a partir de C, C2, L, L2, CL e C2L2. As regressões lineares usando o produto de dimensões CL foram mais eficientes para estimar a AF de V. ferruginea do que os modelos baseados em uma única dimensão (C, L, C2 ou L2). O modelo linear AF = 0,463+0,676 CL forneceu com maior precisão a AF de V. ferruginea em relação aos demais modelos testados. A validação do modelo selecionado revelou elevada correlação entre a área foliar real e a área foliar estimada pelo modelo.
Modelo linear não-destrutivo para estimativa de área foliar de Vernonia ferruginea Less
Keywords: Asteraceae; Cerrado; Savanna; Statistical model; Validation; Asteraceae; Cerrado; Modelos estatísticos; Savana; Validação